Strategies to improve propagation protocol of Philippine native catfish (Clarias macrocephalus) - Bautista, Lemark M
Clarias macrocephalus has been extirpated in most regions in the Philippines and as a preliminary study towards its reintroduction, we aimed at enhancing the growth and reproductive performance of the of the broodstock. several studies have identified thiamine deficiency as a factor in the extirpation of some important fish species in the wild. The present aimed to determine the effects of elevated dietary carbohydrates and benfotiamine, a more bioavailable analog of thiamine (vitamin B1). Three diets were used, namely, a commercial diet specific for catfish was used as the control diet (Com), a high carbohydrate (HC) diet, and a benfotiamine-supplemented HC diet (HCB). Results show that survival of the subadult catfish in captivity for 10 weeks was remarkably high, exhibiting an average of 99% for all three treatments (P>0.05). HCB diet resulted in significantly higher final average body weight (FABW), weight gain (WG), specific growth rate (SGR), and significantly best food conversion ratio (FCR) (P>0.05) than the values for both Com and HC groups (P>0.05). For the reproductive performance, female native catfish fed the HCB diet exhibited significantly heavier ovary and liver (P<0.05) than those female catfish fed either the Com or HC diet (P>0.05). GSI of the female catfish and fecundity were significantly higher in the HCB group (P<0.05) than in the Com or HC group (P>0.05). In the male catfish, testes were significantly heavier in the HCB group (P<0.05) than in the Com or HC diet (P>0.05).HSI, male LW, and LL were significantly higher in the HC and HCB groups (P>0.05) than in the Com group (P<0.05). GSI values of the male catfish were significantly highest in the HCB (P<0.05), followed by the HC group, and significantly lowest in the Com group (P<0.05). The larval survival rate for one week was significantly higher (P<0.05) in the native catfish fed the FCB diet than in those fed the Com or HC diet (P>0.05). In conclusion, elevating dietary carbohydrates in the dit from 7.70% to22.73% (i.e., Com to HC diet, respectively) did not negatively affect the growth and reproductive performance of the catfish. Further supplementation of benfotiamine at 0.02% tothe HC diet enhanced significantly both the growth and reproductive performance of the native catfish (Clarias macrocephalus).